Expression profile of long non-coding RNA in inner Mongolian cashmere goat with putative roles in hair follicles development - Ma, Rong; Shang, Fangzheng; Rong, Youjun; Pan, Jianfeng; Wang, Min; Niu, Shuran; Qi, Yunpeng; Li, Yanbo; Lv, Qi; Wang, Zhiying; Wang, Ruijun; Su, Rui; et al. (Frontiers in Veterinary Science, 2022)
The hair follicle is a complex skin accessory organ, which determines hair growth. Long non-coding RNAs (lncRNAs) have been proven to play an important role in hair follicle development, but their specific mechanism is still unclear. In this study, high-throughput sequencing was used to obtain the expression profiles of lncRNA in the hair follicles of Inner Mongolian cashmere goats at different embryonic stages (45d, 55d, 65d, and 75d), and a total of 6630 lncRNA were identified. According to the rules of hair follicle development, we combined miRNA and mRNA databases (published) and predicted lncRNA-miRNA, miRNA-mRNA, and lncRNA-mRNA interaction pairs in the 45vs75 comparison group. We obtained 516 lncRNA-mRNA, 1011 lncRNA-miRNA, and 7411 miRNA-mRNA relationship pairs. Finally, target genes were analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), and it was found that they were mainly enriched in the Wnt signaling pathway and PI3K-Akt signaling pathway related to hair follicle development, indicating that lncRNA may interact with miRNA/mRNA to directly or indirectly regulate the expression of genes related to hair follicle development. Dual-luciferase reporter gene analysis showed that lncRNA MSTRG.1705.1 could bind to Chi-miR-1, while lncRNA MSTRG.11809.1 had no binding site for Chi-miR-433. In conclusion, this study aims to further analyze the molecular regulation mechanism of hair follicle development and to lay a theoretical foundation for revealing the regulation mechanism of cashmere hair follicle growth..